Modern weapons and military equipment for the issue 2-2023 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Russia’s MiG-31 Foxhounds Proving To Be A Threat To Ukrainian Aircraft; Futuristic Mortar Turret Seen In Action At U.S. Special Ops Base In Syria; Using Grom Standoff Weapons In Ukraine Emerges